Implementasi Metode Ummi dalam Pembelajaran Al-Qur’an di Madrasah Diniyah - Kurniasari, Anis Nila; Ana, Sri; Salma, Kunti Nadiyah (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This article aims to examine the implementation of the Ummi method in Qur'an learning at Madin Fathul Ulum and to identify the factors that influence its implementation. This research uses a qualitative method with a descriptive qualitative approach. Data collection was conducted through interviews, observations, and documentation. Data analysis techniques included data reduction, data presentation, and conclusion drawing. Based on the research findings, the following conclusions were drawn: The implementation of the Ummi method at Madin Fathul Ulum includes: a) Preparation Stage: Teachers prepare syllabi, lesson plans (RPP), teaching aids, and media. b) Implementation Process: This includes opening, delivering material, evaluation, and closing. c) Evaluation Process: Conducted at the beginning, during, and at the end of the learning process. The supporting and inhibiting factors are as follows: Supporting factors include students' Qur'an reading ability, student motivation, media, and teaching aids. Inhibiting factors include uneven student reading abilities, limited time, some uncertified teachers, and a lack of parental support and motivation.